2020
DOI: 10.1111/jocn.15157
|View full text |Cite
|
Sign up to set email alerts
|

“Wow I had no idea”—How job rotation is experienced by nurses caring for elective orthopaedic patients: A qualitative study

Abstract: Aims and objectives To explore gains and impacts of job rotation through the experiences of involved nursing personnel responsible for different parts of care during the elective orthopaedic patient's pathway. Background When patients undergo elective orthopaedic surgery, they encounter nurses from different wards. So far, job rotation has only been described through the experiences of the job rotating nurses. This study includes all involved nursing personnel and bases the job rotation on the pathway of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…This aligns with previous research that has demonstrated that found that nurses who have experienced job rotation tend to exhibit high levels of job satisfaction and job commitment (Alfuqaha et al, 2021; Platis et al, 2021), supporting the notion that exposure to diverse experiences can facilitate the retainment of newly graduated nurses. Moreover, Halberg et al (2020) stressed by rotating nurses across different wards and involving them in various aspects and elements of the patient's pathway, their knowledge and understanding of the entire care process can be expanded. Based on previous research concerning newly graduated nurses, it is hypothesized by the author team that job rotation can be a valuable approach to enhance their professional development and acquisition of skills.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with previous research that has demonstrated that found that nurses who have experienced job rotation tend to exhibit high levels of job satisfaction and job commitment (Alfuqaha et al, 2021; Platis et al, 2021), supporting the notion that exposure to diverse experiences can facilitate the retainment of newly graduated nurses. Moreover, Halberg et al (2020) stressed by rotating nurses across different wards and involving them in various aspects and elements of the patient's pathway, their knowledge and understanding of the entire care process can be expanded. Based on previous research concerning newly graduated nurses, it is hypothesized by the author team that job rotation can be a valuable approach to enhance their professional development and acquisition of skills.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, a study was conducted and found that the job rotation approach is an effective strategy to increase job satisfaction among nurses 21 . Studies suggest that job rotation approach has a direct effect on skills, knowledge, and influence among nurses 8,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Menurut Delpasand et al (2011) dan Halberg et al (2020), pusingan kerja merupakan salah satu faktor untuk meningkat kemahiran dan pengalaman pegawai yang boleh dikaitkan dengan perkembangan kerjaya. Namun pada asasnya, perkembangan kerjaya seseorang adalah bergantung kepada faktor individu itu sendiri dan faktor organisasi.…”
Section: Laluan Kerjaya Pegawai Tldmunclassified